PENGEMBANGAN STANDAR KOMPETENSI JABATAN SALES MARKETING PADA PERUSAHAAN DAGANG KAIN PT X - Adiva Fristasya; Metha Djuwita Supriatna (ITB AAS Indonesia Surakarta, 2024)
PT X is a company that operates in trading textile fields that sells fabric for Muslim’s fashion in Indonesia. As a trading company, the marketing employee position is one of the key positions. However, in 2023 there will be a decline in sales due to the employees occupying these positions not having competence in the field of marketing. It can be avoided if the recruitment process has reference documents, namely competency standards. This research aims to address the issues of the insufficience of competence in sales marketing employees in PT X who are unable to achieve company sales targets. The fact that competency standards are really needed as a basis for employee development and recruitment, therefore in this research, competency standards were formulated using the Spencer competency dictionary with the steps from regional model competency standard (SKKNI). This research was conducted in a descriptive qualitative supported by a literature study to explore and strengthen the phenomenon that happens in PT X. The research results show that sales marketing positions require various competencies such as achievement of orientation level 5, initiative level 4, concern for order level 4, information seeking level 5, customer service orientation level 6, relationship building level 3, and interpersonal understanding level 3.